Pengaruh Kinerja Karyawan terhadap Kepuasan Pelanggan dengan Mediasi Kualitas Layanan di Cafe Terserah Dompu - Danil Pratiwi; Mahmud Mahmud; Ibrahim Jakariah (Jurnal Manajemen Riset Inovasi, 2026)
The primary focus of this study is to investigate how employee performance influences customer satisfaction, with service quality serving as a mediating variable. The study was conducted at Cafe Terserah Dompu using a quantitative approach. From a customer population of unknown size, a sample of 97 respondents was selected using accidental sampling. The sample size was determined using a sample size calculator with a margin of error of 10%. Data analysis employed Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that employee performance has a positive and significant effect on customer satisfaction. Employee performance also has a positive and significant effect on service quality. Furthermore, service quality has a positive and significant effect on customer satisfaction. The results of the mediation test confirmed that service quality mediates the effect of employee performance on customer satisfaction. These findings indicate that optimal staff performance, as conceptualized through the SOBC theoretical framework, can foster the creation of excellent service quality that effectively enhances customer satisfaction and positive experiences at Cafe Terserah Dompu.